1989
DOI: 10.1111/j.1471-4159.1989.tb01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide‐Induced Increases in Deposition of Axonally Transported Glycoproteins in Rat Sciatic Nerve

Abstract: The axonal transport of proteins, glycoproteins, and gangliosides in sensory neurons of the sciatic nerve was examined in adult rats exposed to acrylamide via intraperitoneal injection (40 mg/kg of body weight/day for nine consecutive days). The L5 dorsal root ganglion was injected with either [35S]methionine to label proteins or [3H]glucosamine to label, more specifically, glycoproteins and gangliosides. At times ranging from 2 to 6 h later, the sciatic nerve and injected ganglion were excised and radioactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…There was a 10-15% decrease in body weights of exposed animals within 5 days of dosing. As previously reported (Harry et al, 1989), light microscopy of semi-thin sections of the sciatic, sural, and tibia1 nerves showed a normal population of myelinated fibers. Electron microscopic analysis of these nerves only rarely showed any degenerative changes in myelinated or unmyelinated axons.…”
Section: Clinical and Morphological Observationssupporting
confidence: 86%
See 3 more Smart Citations
“…There was a 10-15% decrease in body weights of exposed animals within 5 days of dosing. As previously reported (Harry et al, 1989), light microscopy of semi-thin sections of the sciatic, sural, and tibia1 nerves showed a normal population of myelinated fibers. Electron microscopic analysis of these nerves only rarely showed any degenerative changes in myelinated or unmyelinated axons.…”
Section: Clinical and Morphological Observationssupporting
confidence: 86%
“…The acrylamide-induced deficit of labelled glycoprotein in myelinated axons could be accounted for by a block of a processing step at the level of glycosylation, or further along at the level of commitment of glycoproteins to rapid transport down myelinated axons. In our previous study (Harry et al, 1989), we reported that exposure of rats to acrylamide altered the transport kinetics of labelled glycoproteins. This transport abnormality was evidenced by a marked attenuation of the initial crest of transported material.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The neurotoxic action of AA was suggested to be due to effects on cells of the central and peripheral nervous system including changes in cellular metabolism (Howland et al, 1980;Brimijoin and Hammond,1985;Medrano and LoPachin, 1989;Exon, 2006), changes in gene transcription and protein synthesis (Cavanagh and Nolan, 1982a,b;Cavanagh, 1982;Cavanagh and Gysbers, 1983;Bisby and Redshaw, 1987;Lin et al, 2000;El-Alfy et al, 2011;Seale et al, 2012), effects on neurotransmitter levels and turn-over (Dixit et al, 1981;Uphouse and Russell, 1981;Aldous et al, 1983;Shi et al, 2012), binding to cellular proteins including damage to microtubular and neurofilamental proteins (Hashimoto and Aldridge, 1970;Tanii and Hashimoto, 1983;Carrington et al, 1991;Reagan et al, 1994;Abou-Donia, 1996, 1997;Lapadula et al, 1989;Xiwen et al, 1992), changes in ion distribution (Lehning et al, 1998;LoPachin and Lehning, 1994), and axonal transport (Chretien et al, 1981;Miller and Spencer, 1984;Gold et al, 1985;Moretto and Sabri, 1988;Logan and McLean, 1988;Harry et al, 1989;Sabri and Spencer, 1990;Martenson et al, 1995;Sickles et al, 1995Sickles et al, ,1996Stone et al, 2001). However, the minimal effects of AA-treatment, by up to a maximally tolerated dose, on: (i) gene expression related to cholinergic, noradrenergic, dopaminergic, GABAergic, or glutamatergic neurotransmitter systems; (ii) neurotransmitter levels related ...…”
Section: Mode Of Action Of Neurotoxicitymentioning
confidence: 99%